Conflicting Patterns of Thought in the Russian Debate on Transition: 1992-2002 - Joachim Zweynert (Hamburg Institute of International Economics (HWWA), 2006)
The present study is a continuation of an earlier paper by the same author dealing with the economic debates in the Soviet Union between 1987 and 1991 (HWWA Discussion Paper 324; Europe-Asia Studies vol. 58, no. 2). After there had been a paradigm shift in Russian economics around 1990, in the period under review the Russian economists increasingly returned to the path-dependent shared mental models prevailing in their country. In particular, the old debate between “Westernizers“ and Slavophiles was forcefully revived after the liberal reform concept seemed to have failed to solve the socioeconomic problems. The conflict between these camps has not yet been settled. This, I argue, makes it difficult to predict the further development of Russia's economic and political order.
Keywords: B25; Z10; P51; 330; Institutions; Economic Development; Transition; Systemtransformation; Russland